Representation of Tawakkal and Peace of Mind in Budi Utami's Jawi Syi'ir Book - Syihabul Khoir; Darni (Raja Zulkarnain Education Foundation, 2026)
The mental health crisis is a global phenomenon that continues to intensify alongside the growing complexity and pressures of modern life, particularly affecting young people, minority communities, and individuals from lower socio-economic backgrounds who often face limited access to holistic mental health services. Western psychological approaches, which tend to emphasize cognitive, behavioral, and individual aspects, are considered insufficient to fully address the spiritual dimension that plays a crucial role in shaping mental health, especially within religious societies. This study aims to examine the representation of the concept of tawakkal and its implications for inner tranquility in Syi’ir Jawi Budi Utami as part of the corpus of Nusantara Islamic literature, from the perspective of Islamic psychology. This research employs a qualitative approach through library research, using Syi’ir Jawi Budi Utami as the primary data source and secondary data derived from literature on Islamic psychology, Sufism, and relevant scholarly articles. Data analysis is conducted using content analysis, deepened through a hermeneutic approach to uncover the psychospiritual meaning of tawakkal. The findings indicate that the concept of tawakkal in Syi’ir Jawi Budi Utami is represented as a mechanism of soul purification (tazkiyat an-nafs) that balances human effort (ikhtiar) and surrender to God, thereby contributing to the formation of inner tranquility (thuma’ninah al-qalb). This concept has the potential to serve as an alternative spiritual approach in strengthening mental health based on the values of Nusantara Islam.